Nanoscale coexistence of polar-nonpolar domains underlying oxygen storage properties in Ho(Mn,Ti)O_{3+δ} - Hiroshi Nakajima; Kento Uchihashi; Hirofumi Tsukasaki; Daisuke Morikawa; Hiroyuki Tanaka; Tomohiro Furukawa; Kosuke Kurushima; Jun Yamasaki; Hiroki Ishibashi; Yoshiki Kubota; Atsushi Sakuda; Akitoshi Hayashi; et al. (Physical Review Research, 2023)
Hexagonal manganese oxides RMnO_{3} (R=Y, Ho–Lu, Sc, and In) show intriguing topological ferroelectric domain walls with variable conductivity, leading to domain wall engineering. Despite the numerous experimental studies on these polar nanoscale structures, controlling ferroelectric domains has not been sufficiently investigated. Here, we reveal the unprecedented coexistence of polar-nonpolar nanoscale domains that can be formed by substituting titanium ions in HoMnO_{3}. Unusual polar nanoscale domains are embedded in nonpolar domains with different crystallographic symmetry. This polar-nonpolar coexisting structure is naturally assembled by adjusting the lattice length during a solid-state reaction process. Furthermore, this comprehensive study reveals that the reversible microstructural change with a nonpolar-polar transition is strongly correlated with the oxygen storage properties in Ho(Mn,Ti)O_{3+δ}. The present results provide important insight into the nanoscale polar-nonpolar domain coexistence in functional rare-earth manganese oxides, RMnO_{3}.